MANAGEMENT OF CHARACTER LEADERSHIP STUDENT LEADERSHIP IN SECONDARY MIDDLE SCHOOL NSQ CITY CIREBON - Siti Rochanah (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
This research was conducted in Junior high school NSQ Cirebon West Java, which aims to know and to obtain an overview of leadership character education for student. This research was conducted in June to October 2017. The approach used is a qualitative approach with descriptive method. Data collection was done through an interview, observation, and study documentation. A source of data from this research comes from principal's and supports several informants is teacher, and student. Teamwork formed by the principal's consist of teachers, committee and parents. The planning of leadership character building of students in Junior high school NSQ is done through the mechanism of work meeting at the beginning of the school year. Organizing the guidance of student leadership character in Junior high school NSQ is done by making organizational structure that contains the roles and responsibilities in carrying out the guidance of student leadership character. The implementation of leadership character building of students in Junior high school NSQ is done through intra-school students organization program, Scouting and Basic Training of Student Leadership. The supervision of the leadership character building of the students in Junior high school NSQ is done directly by the principal and the board of the Foundation. Keywords: leadership, character education.